A novel two‐parameter class of optimized hybrid block methods for integrating differential systems numerically. Issue 6 (12th December 2021) - Singh, Gurjinder; Garg, Arvind; Singla, Rajat; Kanwar, Vinay
Abstract: In this article, a two‐parameter class of hybrid block methods for integrating first‐order initial value ordinary differential systems is proposed. The methods exhibit hybrid nature which helps in bypassing the first Dahlquist barrier existing for linear multistep methods. The approach used in the development of a class of methods is purely interpolation and collocation technique. The class of methods is based on four intra‐step points from which two intra‐step points have been optimized by using an optimization strategy. In this optimization strategy, the values of two intra‐step points are obtained by minimizing the local truncation errors of the formulas at the points x n + 1 / 2 and x n + 1 .The order of accuracy of the proposed methods is six. A method as a special case of this class of methods is considered and developed into a block form which produces approximate numerical solutions at several points simultaneously. Further, the method is formulated into an adaptive step‐size algorithm using an embedded type procedure. This method which is a special case of this class of methods has been tested on six well‐known first‐order differential systems.